Kandang Kambing Ramah Lingkungan pada Lahan Fasum Pondok Maritim - Sri Dwiyanti; Farid Baskoro; Miftahur Rohman (Politeknik Piksi Ganesha Indonesia, 2025)
The purpose of this Community Service is to optimize the utilization of public facilities in Pondok Maritim RT05 RW06 Balasklumprik Wiyung Surabaya. Public facilities that have been used for urban farming so far by raising goats. Urban farming is the activity of raising livestock in and around large cities (metropolitan) or small cities to obtain food or other needs and increase income. This PKM method provides a touch of technology by creating an environmentally friendly goat pen design (Kakamraling) that has aesthetic value and does not pollute the environment (smell). The results of the community service The goat pen will be specially designed with a separator/separator system between feces and urine. Which is directly put into the container and will be harvested periodically into organic fertilizer based on cohe (animal waste) and liquid organic fertilizer (urine). The separator is in the form of a gutter that will immediately separate into storage containers. Thus, community members can increase their income from 1) raising goats, 2) selling organic cohe fertilizer, and 3) selling organic goat urine fertilizer.